Закономірності електромагнітних процесів безконтактної системи збудження асинхронізованого генератора за схемою у дві зірки на базі трифазно-трифазного модулятора напруги - Василів, Карл Миколайович (НТУ "ХПІ", 2016)
Встановлено закономірності перебігу електромагнітних процесів, які відбуваються у безконтактній системі збудження асинхронізованого генератора на базі каскадного трифазно-трифазного модулятора напруги на предмет можливості збільшення двозонного ковзання генератора. Запропоновано спосіб корегування параметрів роторів машин модулятора, який дає змогу стабілізувати роботу комутатора для практично необхідних значень ковзання. Досягнуто значного розширення діапазону ковзання – до двох десятих із забезпеченням роботопридатності асинхронізованого генератора.

By means of mathematical modeling there have been studied regularities of electromagnetic processes taking place in the contactless excitation system of an asynchronous generator based on cascade, threephase-threephase voltage modulator. There have been found the regularities of these processes with the aim to examine the impact of changes in slip resistance of the generator on the stability of the switch op eration and, as a result, on the stability of the excitation system and the generator as a whole. There is offered a method of adjusting parameters of the modul ator rotor machine that allows stabilizing the switch and excitation system operation to get the sliding values sufficient for the generator to work in practice. The sliding range has been greatly expanded, up to two tenths, ensuring operation suitability of the asynchronous generator in this range.
Regularities of electromagnetic processes in the contactless excitation system of an asynchronous generator following a two-star scheme based on a threephase-threephase voltage modulator
Keywords: асинхронізований генератор; модулятор напруги; комутатор; безконтактна система збудження; ковзання; asynchronous generator; voltage modulator; switch; contactless excitation system; slide